Homoallylic amines by reductive inter- and intramolecular coupling of allenes and nitriles - Wipf, Peter; Manojlovic, Marija D. (Beilstein Journal of Organic Chemistry, 2011)
The one-pot hydrozirconation of allenes and nitriles followed by an in situ transmetalation of the allylzirconocene with dimethylzinc or zinc chloride provides functionalized homoallylic amines. An intramolecular version of this process leads to 3-aminotetrahydrofurans and 3-aminotetrahydropyrans.
Keywords: allene; 3-aminotetrahydrofurans; 3- and 4-aminotetrahydropyrans; hydrozirconation; nitrile; transmetalation